Facility-Level Factors and Racial Disparities in Cardiopulmonary Resuscitation within US Dialysis Clinics. Issue 6 (30th June 2022) - Pun, Patrick H.; Svetkey, Laura P.; McNally, Bryan; Dupre, Matthew E.
Key Points: Clinics caring for Black versus White cardiac arrest patients have significant differences in quality, resources, and patient case mix. Accounting for differences in clinic characteristics between Black versus White cardiac arrest patients did not reduce race disparities in cardiopulmonary resuscitation. Relative to younger patients, older Black patients were less likely to receive cardiopulmonary resuscitation in dialysis clinics compared with older White patients. Visual Abstract: Abstract : Background: Cardiac arrest occurs frequently in outpatient dialysis clinics, and immediate cardiopulmonary resuscitation (CPR) provision improves patient outcomes. However, Black patients in dialysis clinics receive CPR from clinic staff less often compared with White patients. We examined the role of dialysis facility resources and patient factors in the observed racial disparity in CPR receipt and automated external defibrillator application. Methods: This was a retrospective cohort study linking the National Cardiac Arrest Registry to Enhance Survival and Medicare Annual Dialysis Facility Report registries from 2013 to 2017. We identified patients experiencing cardiac arrests within US outpatient dialysis clinics via geolocation matching ( N =1554). Differences in facility size, quality, staffing, and patient-related factors were summarized and compared according to patient race. Multilevel multivariable logistic regression models including these factors were used to examine the influence of these factors on the observed disparity in CPR rates between Black and White patients. Results: Compared with White patients, Black cardiac arrest patients dialyzed in larger facilities (26 versus 21 dialysis stations; P <0.001), facilities with fewer registered nurses per station (0.29 versus 0.33; P <0.001), and facilities with lower quality scores (# citations 6.8 versus 6.3; P =0.04). Facilities treating Black patients cared for a higher proportion of patients with a history of cardiac arrest (41% versus 35%; P <0.001), HIV/hepatitis B, and Medicaid-enrolled patients (15% versus 11%; P <0.001). Even after accounting for these differences and other covariates, the racial disparity for CPR in Black versus White patients persisted (OR=0.45; 95% CI, 0.27 to 0.75). The racial disparity in CPR was greater among older patients compared with younger patients (interaction P =0.04). Conclusions: The racial disparity in CPR delivery within dialysis clinics was not explained by differences in facility resources and quality. Reducing this disparity will require a multifaceted approach, including developing dialysis clinic-specific protocols for CPR and addressing potential implicit bias.